Quality of life of patients treated with robotic surgery in the oral and maxillofacial region: a scoping review of empirical evidence - Dhanushka Leuke Bandara; Kehinde Kazeem Kanmodi; Afeez Abolarinwa Salami; Timothy Olukunle Aladelusi; Ayodhya Chandrasiri; Jimoh Amzat; Ruwan Duminda Jayasinghe (BMC, 2024)
Abstract Background There is a blooming trend in the application of robotic surgery in oral and maxillofacial care, and different studies had evaluated the quality of life (QoL) outcomes among patients who underwent robotic surgery in the oral and maxillofacial region. However, empirical evidence on the QoL outcomes from these procedures is yet to be mapped. Thus, this study was conducted to evaluate the available scientific evidence and gaps concerning the QoL outcomes of patients treated with robotic surgery in the oral and maxillofacial region. Methods This study adopted a scoping review design, and it was conducted and reported based on the Arksey and O'Malley, PRISMA-ScR, and AMSTAR-2 guidelines. SCOPUS, PubMed, CINAHL Complete, and APA PsycINFO were searched to retrieve relevant literature. Using Rayyan software, the retrieved literature were deduplicated, and screened based on the review's eligibility criteria. Only the eligible articles were included in the review. From the included articles, relevant data were charted, collated, and summarized. Results A total of 123 literature were retrieved from the literature search. After deduplication and screening, only 18 heterogeneous original articles were included in the review. A total of 771 transoral robotic surgeries (TORSs) were reported in these articles, and the TORSs were conducted on patients with oropharyngeal carcinomas (OPC), recurrent tonsillitis, and obstructive sleep apnoea (OSA). In total, 20 different QoL instruments were used in these articles to assess patients' QoL outcomes, and the most used instrument was the MD Anderson Dysphagia Inventory Questionnaire (MDADI). Physical functions related to swallowing, speech and salivary functions were the most assessed QoL aspects. TORS was reported to result in improved QOL in patients with OPC, OSA, and recurrent tonsillitis, most significantly within the first postoperative year. Notably, the site of the lesion, involvement of neck dissections and the characteristics of the adjuvant therapy seemed to affect the QOL outcome in patients with OPC. Conclusion Compared to the conventional treatment modalities, TORS has demonstrated better QoL, mostly in the domains related to oral functions such as swallowing and speech, among patients treated with such. This improvement was most evident within the initial post-operative year.